Sirt2 ablation exacerbates Sod1 knockout-induced progeroid phenotype in mice - Anke Geng; Xiaona Wang; Zhenkai Wu; Zhihao Liu; Xiao Huang; Xiyue Wang; Xiaoxiang Sun; Yingjie Wang; Jiayu Chen; Ying Jiang; Huanyin Tang; Zhiyong Mao (Redox Biology, 2025)
The free radical theory of aging suggests that oxidative stress from free radicals contributes to aging. While free radicals cause DNA damage and cellular dysfunction, they also regulate essential signaling pathways. This duality complicates direct testing of the theory in mice, as demonstrated by the minor lifespan impact of Sod1 knockout. We hypothesize that base excision repair mechanisms, that involve SIRT2, a longevity-associated SIRTUIN family member, may mitigate excessive free radical effects. Our study found that Sirt2−/−Sod1−/− double-knockout mice exhibited significantly reduced lifespan and progeroid phenotypes, including spinal curvature and tissue degeneration. These mice displayed increased aging-related gene expression, cellular senescence, enlarged spleens, elevated cytokines, and immune dysregulation, potentially leading to cytokine storm-related deaths. Additionally, Sirt2 overexpression rescued genomic instability caused by Sod1 deficiency in cells. These findings refine free radical theory of aging and highlight SIRT2 as a target for enhancing DNA repair and mitigating aging-associated phenotypes.